Estudo da interação entre silício e alumínio extraídos do vidro na presença de soluções para nutrição parenteral - Bortoluzzi, Fabiana (2003)
Silicon is a non-metal essential to the living organisms due to its role in the tissues and bones. The most important biological forms of silicon are the amorphous silica and the monomeric silicic acid. Only the monomeric silicic acid is absorbed by the gastrointestinal tract. Aluminum is an omnipresent element in the environment. Since the 70’s it has been related to some neurodegenerative diseases, mainly in endstage chronical renal patients. Silicon and aluminum are constituents of glasses and glass is the most important container material for medicines and, among them, solutions for parenteral nutrition. The presence of aluminum in solutions for parenteral nutrition has been monitored lately due to the toxicity risk for patients that receive this kind of treatment. Parenteral solutions are used for patients that cannot be fed orally, including pre-term infants and surgical patients. The administration of parenteral nutrition solutions contaminated by aluminum for long periods can lead to intoxication and subsequent neurological and bone problems. The limit for aluminum in solutions for parenteral nutrition was established by the FDA as 25 μg/L. However, high levels have been found in many formulations. The aim of this work was the quantification of silicon and aluminum in these solutions, as well as the evaluation of the “free-aluminum fraction” because silicic acid is able to bind aluminum tightly. Silicon and aluminum already present in the substances were measured. The extraction of these elements from the glass containers during the heating for the sterilization of the solutions was investigated by storing each component of the parenteral nutrition solutions individually in sealed glass ampoules, submitting them to the sterilization procedure and measuring the elements after that. They were measured either by atomic absorption spectrometry or spectrophotometry. The assays showed that all the substances are contaminated by both elements, but it is the heating for sterilization with the consequent interaction with the glass that is responsible for high levels of contamination. It could be observed that the glass dissolution and the silicon and aluminum extraction is related to the nature of the species in contact with the glass surface. Whereas amino acids shoed low levels of contamination, saline solution and mainly basic solutions presented the highest levels. The extraction mechanism can be related to the simple glass dissolution, to an ion-exchange process or to an affinity of the species for silicon or aluminum. The results showed that in those solutions where the silicon content were high the free aluminum was very low, comparing with the total aluminum measured in the solution. This effect is probably due to the formation of hydroxyaluminumsilicates (HSA). The simultaneous presence of silicon and aluminum can turn the aluminum not available to be absorbed by the human body.